Online art therapy in elementary schools during COVID-19: results from a randomized cluster pilot and feasibility study and impact on mental health - Catherine Malboeuf-Hurtubise; Terra Léger-Goodes; Geneviève A. Mageau; Geneviève Taylor; Catherine M. Herba; Nicholas Chadi; David Lefrançois (BMC, 2021)
Abstract Background Emerging literature on the current COVID-19 crisis suggests that children may experience increased anxiety and depression as a result of the pandemic. To prevent such school and mental health-related problems, there is a timely need to develop preventive strategies and interventions to address potential negative impacts of COVID-19 on children's mental health, especially in school settings. Results from previous child clinical research indicate that art-based therapies, including mindfulness-based art therapy, have shown promise to increase children's well-being and reduce psychological distress. Objective The goal of the present pilot and feasibility study was to compare the impact of an emotion-based directed drawing intervention and a mandala drawing intervention, on mental health in elementary school children (N = 22), in the context of the COVID-19 pandemic. Both interventions were group-based and delivered online and remotely. A pilot study using a randomized cluster design was implemented to evaluate and compare both interventions in relation to child anxiety, depression, inattention and hyperactivity symptoms. Results Analyses of covariance revealed a significant effect of the type of drawing intervention on levels of inattention, after controlling for baseline levels. Participants in the emotion-based directed drawing group showed lower inattention scores at post-test, when compared to participants in the mandala group. Post-hoc sensitivity analyses showed significant decreases in pre-to-post scores for levels of hyperactivity for the complete sample. Conclusion Overall, results from this pilot and feasibility study showed that both an emotion-based directed drawing intervention and a mandala drawing intervention may be beneficial to improve mental health in elementary school children, in the context of the current COVID-19 pandemic. From a feasibility standpoint, results indicate that the implementation of both interventions online and remotely, through a videoconference platform, is feasible and adequate in school-based settings. Further work incorporating larger sample sizes, longitudinal data and ensuring sufficient statistical power is warranted to evaluate the long-term impact of both interventions on children's mental health.